2005
DOI: 10.1002/env.736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimized variable area transect sampling using totally enumerated field data sets

Abstract: SUMMARYPlotless density estimators (PDEs) can be efficient alternatives to quadrat sampling for estimating the density of stationary objects. Variable area transect (VAT) sampling had been identified, and optimized relative to effort, in previous Monte Carlo simulated population studies as a low-labor field method that demonstrated superior estimation properties among many PDEs considered. However, natural populations tend to be much more complex and less predictable in spatial distribution than computer gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…La méthode a l'avantage de permettre l'exploration des résultats indépendamment de la surface échantillonnée (Parker, 1979 ;Engeman et al, 2005).…”
Section: Materiels Et Methodesunclassified
“…La méthode a l'avantage de permettre l'exploration des résultats indépendamment de la surface échantillonnée (Parker, 1979 ;Engeman et al, 2005).…”
Section: Materiels Et Methodesunclassified
“…Furthermore, it is often recommended to use a strip as wide as possible so as to increase the detection efficiency (e.g. Engeman et al, 2005, for variable area transect sampling). In our case study, we made a field survey to determine the maximum distance at which 100% of attacked trees could be sighted from the forest road (D max ) and showed that it varied with tree density.…”
Section: Strip Sampling Along Stand Edgesmentioning
confidence: 99%
“…It seems to offer a good compromise between the accuracy of the estimates and investment in field work. It has been successfully tested on different crop damages of various densities but only at the stand scale (Engeman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The method suggested by Borders et al [4] of sampling a fixed number of trees along a variable section of a plantation row may be similar in principle to a variable-length transect. Several simulation studies indicated positive results from variable area transect sampling ( [31][32][33]). However, variable area transects were found to have significant bias towards a clustered spatial distribution by Engman et al [34].…”
Section: Introductionmentioning
confidence: 99%